Long-term placement of lumen-apposing metal stent after endoscopic ultrasound-guided duodeno- and jejunojejunal anastomosis for direct access to excluded jejunal limb - Donatelli, Gianfranco; Cereatti, Fabrizio; Spota, Andrea; Danan, David; Tuszynski, Thierry; Dumont, Jean-Loup; Derhy, Serge (Endoscopy, 2020)
Background Management of biliary disorders in patients with altered anatomy may be challenging. Endoscopic ultrasound (EUS)-guided gastrointestinal anastomosis using a lumen-apposing metal stent (LAMS) was introduced to allow endoscopic retrograde cholangiography (ERC) in such cases. However, the appropriate stent indwelling time remains uncertain. We report long-term LAMS deployment after duodenojejunal or jejunojejunal anastomosis (EUS-DJA) to allow endoscopic reinterventions in cases of recurrences.Methods 11 consecutive patients underwent EUS-DJA with long-standing LAMS between January 2017 and December 2018. Over a 12-month period, ERC treatment was carried out with multiple endoscopic sessions across the DJA.Results Technical success was 91 % (10/11) for EUS-DJA and 100 % for ERC. Four patients presented stricture recurrence at a mean of 489 days (standard deviation [SD] 31.7) after the end of ERC treatment. A novel ERC across the LAMS anastomosis was feasible in all cases. At a mean of 781 days (SD 253.1), all LAMS remained in place with no evidence of complications.Conclusion Long-term LAMS placement after EUS-DJA may be feasible and safe for direct access to the excluded limb.